The Role of Authorial Intent in Determining Verbal Irony and Metaphor - Katz, Albert N.; Lee, Christopher J. (Metaphor and symbolic activity, 1993)
Three groups of participants rated the authorial intent to endorse or reject the truth-value, the degree of irony, or metaphoricity of target utterances contained in brief anecdotes. Target utterances could be interpreted either literally or figuratively; a figurative resemblance was suggested by having the utterance echo an earlier usage. The anecdotes manipulated (a) congruence of the utterance with observational fact and (b) audience type. Type of audience depended on whether all listeners (nonpolarized audience), or only some listeners (polarized audience) were aware that the target utterance echoed an earlier utterance. Results supported the hypothesis that authorial intent would affect the relative degree of irony and metaphoricity perceived by participants: Endorsements were perceived as conveying a metaphoric message, whereas rejections were perceived as ironic. Congruent usage was taken as endorsement of a truth-value and incongruent usage was taken as rejection of a truth-value. Incongruent utterances perceived as rejections of truth-value were seen as especially ironic when made in the presence of a polarized audience. Finally, degree of irony was dependent on both the comprehension of the figurative resemblance expressed in the utterance and understanding the social convention implied by the use of a polarized audience. This suggests that the comprehension of irony requires a processing stage not required for comprehension of metaphor. The implications of the results for pretense, mention, and echoic reminding theories of irony are discussed.